Heteronuclear soliton molecules in optical microresonators - Wenle Weng (Nature Portfolio, 2020)
Molecules of solitons provide insight into fundamental interactions between them and the underlying nonlinear system. The reported heteronuclear molecules, comprised of dissipative solitons with distinct frequencies, temporal widths, and energies enter the multistability regime and yield in interlocked frequency combs.